Effects of Intracerebroventricular Infusion of Somatostatin‐14 on Peripheral Glucoregulation in Dogs. (January 2014) - Yavropoulou, M. P.; Kotsa, K.; Pikilidou, M.; Keisisoglou, I.; Yovos, J. G.
<x xml:space="preserve">Abstract</x> Somatostatin (SST) is an inhibitory hormone that regulates numerous biological processes and circulates in two bioactive isoforms: SST‐14 and SST‐28. SST‐14 is the predominant form in the hypothalamus and regulates the secretion of growth hormone (GH) (directly) and of thyroid‐stimulating hormone (indirectly). In the periphery, SST is a potent inhibitor of glucagon and insulin secretion. In the present study, we aimed to investigate the effect of i.c.v. administration of SST‐14 on glucose metabolism. Twenty healthy adult dogs randomly received either a bolus i.c.v. infusion of 5, 25 or 50 μg of SST‐14 or an equivalent amount of artificial cerebrospinal fluid through an epicranial apparatus during fasting. The same experiment was repeated during concomitant intraduodenal infusion of glucose solution through a Mann–Bollman fistula. Serum levels of glucose, insulin and glucose‐dependent insulinotrophic peptide (GIP), plasma SST and serum GH levels were assayed. Circulating levels of SST and GH did not change significantly during i.c.v. infusions. Bolus infusion of 50 μg of SST‐14 produced an increase in serum glucose levels at 10 min (94 ± 2.5 mg/dl at baseline versus 101 ± 3 mg/dl, P = 0.04) and significantly suppressed insulin levels, reaching maximal suppression at 60 min after infusion (9 ± 1.3 μIU/ml at baseline versus 4.6 ± 0.5 μIU/ml P = 0.04) in fasting animals. Similar results were obtained during intraduodenal infusion of glucose through a Mann–Bollman fistula. GIP levels did not change significantly during i.c.v. administration of SST‐14. Intracerebroventricular infusion of SST‐14 increases glucose and suppresses insulin levels in the periphery independently of circulating SST levels.